Steam and Microwave Pretreatments in the Preparation of Bioethanol from Sugar Palm Kernel - Nyoman J Wistara; Martua YS Nababan; Rahmi N Hidayah (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
It is paramount to develop bioethanol production based on the utilization of less important carbohydrate based feedstock such as the sugar palm kernel. In the present works, the kernel powder of sugar palm was hydrolyzed by enzymatic and acidic procedures heated either by autoclaving or microwaving. Fermentation of the resulting reducing sugars was then carried out by Saccharomyces cerevisiae at the concentration of 3, 10, and 17% for 24, 48, and 72 hours. It was found that the highest hydrolysis efficiency was by autoclaved acid hydrolysis (92.52%). On the other hand, the highest fermentation efficiency was obtained by 24 hours fermentation with a 17% S. cerevisiae of the resulting sugar from autoclaved enzymatic hydrolysis (97.36%), and the highest ethanol yield was obtained from autoclaved acid hydrolysis fermented for 72 hours with 17% S. cerevisiae (76.49%).  Keywords: bioethanol, fermentation, hydrolysis, S. cerevisiae, sugar palm kernel